Left Atrial Appendage Giant Aneurysm- A Case Report - Hossain, Md Akhter; Badruzzaman, Md; Kabir, Md Mainul; Islam, Md Jahirul; Masud, Md Rowshon (Bangladesh Heart Journal, 2022)
Abstract not available Bangladesh Heart Journal 2022; 37(1): 81-83